1992
DOI: 10.1002/polb.1992.090301309
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropy of polymeric films measured by waveguide propagation mode determination

Abstract: Extruded thin films of a liquid‐crystalline charge‐conjugated rigid‐rod polymer poly(p‐phenylenebenzobisthiazole), PBT, and a semicrystalline thermoplastic polyethylene‐terephthalate (Mylar) were fabricated and examined for film thickness, refractive index, and linear attenuation coefficient. Optical waveguide modes were successfully induced on the polymeric films using a prism coupler at λ = 633 and 1300 nm. Highly consistent thickness values were obtained for the polymeric films. In addition, the anisotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Various new conjugated polymers have been designed and synthesized for efficient light emission or charge transfer 5–8. As a kind of conjugated polymer, poly( p ‐phenylene benzobisthiazole) (PBZT), is well known for its excellent mechanical properties (high tensile strength and modulus), high chemical and thermo‐oxidative resistance,9 and large and ultrafast third‐order nonlinear optics (NLO) response 10–13. However, the high degree of molecular rigidity in polymer backbones and strong intermolecular interactions give rise to the insolubility of PBZT in common organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Various new conjugated polymers have been designed and synthesized for efficient light emission or charge transfer 5–8. As a kind of conjugated polymer, poly( p ‐phenylene benzobisthiazole) (PBZT), is well known for its excellent mechanical properties (high tensile strength and modulus), high chemical and thermo‐oxidative resistance,9 and large and ultrafast third‐order nonlinear optics (NLO) response 10–13. However, the high degree of molecular rigidity in polymer backbones and strong intermolecular interactions give rise to the insolubility of PBZT in common organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The nonresonant linear susceptibilities XX (1) and Y Y (1) are calculated from the extraordinary and ordinary refractive indices ͑n e and n o ͒ measured at a wavelength of 632.8 nm ͑Ref. 11͒ by using the relation of n e,o 2 Ϫ1ϭ2 XX,Y Y (1) . 27 Compared to the linear susceptibilities, the NLO susceptibilities show a stronger dependence on the fabrication surface pressure.…”
Section: Surface Pressure Dependence Behaviorsmentioning
confidence: 99%
“…The extended chain also allows delocalization of the -electrons along the polymer backbone, thus offering high potential for electrical and optical applications. [5][6][7][8] Although a simple picture of the PBZT molecule is a fully extended rod-like one, several studies 9 -12 have suggested that the molecules may possess considerable flexibility. The flexibility may arise from the out-of-plane bending of PBZT main chain, thus forming a ribbon-like chain conformation.…”
Section: Introductionmentioning
confidence: 99%